ChemInform Abstract: Asymmetric Cyanoethoxy Carbonylation Reaction of Aldehydes Catalyzed by a TiIV Macrocyclic Complex: An Efficient Synthetic Protocol for β‐Blocker and α1‐Adrenergic Receptor Agonists. Issue 45 (14th October 2013) - Sadhukhan, Arghya; Choudhary, Manoj K.; Khan, Noor‐ul H.; Kureshy, Rukhsana I.; Abdi, Sayed H. R.; Bajaj, Hari C.
Abstract A new class of the macrocyclic ligands of the type (I) is uncovered.